Local Wisdom and Economic-Conservation Strategy in Communities Affected by Natural Disasters - Maring, Prudensius; Pramegia, Ahmad (Action Research Literate, 2024)
Community interaction with the natural environment is reflected through the local wisdom implemented by the community. This is not free from the parties' interests in natural resources. Exploitative behavior or otherwise maintaining ecological and socio-economic balance in the natural environment arises from the various interests of the parties. Such conditions raise the question: How can society's socio-economic strategies be strengthened so that harmonious relations between humans and nature are maintained through a balance of ecological-conservation and socio-economic interests? This research uses a qualitative approach by collecting data through interviews and observation. The research results show that people living in areas prone to natural disasters in the form of earthquakes and landslides have a pattern of relationship with their natural environment in socio-economic activities. Efforts to escape the impact of natural disasters are experiencing obstacles because the community's socio-economic strategies and activities rely on agriculture and plantations which are directly related to the condition of natural resources. In this situation, it is necessary to improve and strengthen community economic activities in the fields of agriculture, plantations and collaboration at the community level.